Ion Exchange Kinetics of Aniline with Gel Type Sulphonic Acid Cation Exchange Resins: Mechanism of Uptake - Bhat, C.V.; Intodia, Kumud; Vardia, Jitendra (Asian Journal of Chemistry, 2010)
The mechanism of uptake of aniline by Dowex 50W X8 (-100,+200) resin in H+ form from different pH medium and different composition of aqueous methanolic solvent medium has been studied. The mechanism of uptake of aniline takes place through particle diffusion and chemical reaction, the latter predominating in the earlier part, the former in the middle part and neither in the later part of the process of uptake.